Peningkatan Kreativitas Seni Tari melalui Pelatihan Gerak Tari Tradisional/Kreasi NTT bagi Siswa-Siswi SMAN 3 Fatuleu - Anita Papadja; Yosefina Metan; Dekris Apriano Taek (I-Com: Indonesian Community Journal, 2025)
ABSTRACT This Community Service aims to increase dance creativity among students at SMAN 3 Fatuleu through training in traditional dance movements and modern creations from East Nusa Tenggara (NTT). The method used consists of practical and theoretical approaches and involves intensive training which includes basic NTT Traditional and Creative dance techniques. Regarding the practical approach in this activity, one of the professional dance trainers involved 30 students. As a result of this activity, students performed in creative artistic activities with confidence. It is hoped that this activity will not only contribute to increasing students' creativity but also strengthen their love for local culture.